Exploring sustainability oriented innovations in tourism: insights from ecological modernization, diffusion of innovations, and the triple bottom line - Muhammad Fikry Aransyah; Bambang Hermanto; Anang Muftiadi; Hera Oktadiana (Cogent Social Sciences)
Sustainability-oriented innovations (SOIs) are reshaping the tourism industry by addressing environmental, economic, and social challenges. This study synthesises existing research on the impacts of SOIs in tourism through a bibliometric analysis of 88 studies from Scopus. Using Ecological Modernisation Theory (EMT), Diffusion of Innovations (DoI) Theory, and Triple Bottom Line (TBL) Theory, the research highlights the contribution of SOIs to sustainable tourism development. The findings indicate that SOIs enhance environmental sustainability by promoting resource conservation and pollution reduction via green technologies. Economically, SOIs improve financial performance, operational efficiency, and competitiveness while generating revenue through green certifications and eco-labels. Socially, they foster community involvement, customer satisfaction, and social equity. Quantitative methods, such as surveys and regression analysis, are predominant in existing research, complemented by qualitative and mixed-method approaches. This study also identifies critical gaps in the literature, including the long-term impacts of SOIs, the role of technology and green finance, and the effectiveness of green certifications. Addressing these gaps could guide policymakers, tourism practitioners, and stakeholders in advancing sustainable practices and policies. The findings underscore the potential of SOIs to drive sustainable development in tourism and offer valuable insights for future research directions.